Elevation of boiling point of coffee extract - Telis-Romero, Javier [UNESP]; Cabral, R. A F [UNESP]; Kronka, G. Z. [UNESP]; Telis, V. R N [UNESP] (FapUNIFESP (SciELO), 2002)
The rise in boiling point of coffee extract was experimentally measured at soluble solids concentrations in the range of 9.2 to 52.4°Brix and pressures between 5.8 × 103 and 9.4 × 104 Pa (abs.). Different approaches to representing experimental data, including the Dühring's rule, the Antoine equation and empirical models proposed in the literature were tested. In the range of 9.2 to 16.2°Brix, the rise in boiling point was nearly independent of pressure, varying only with extract concentration. Considerable deviations of this behavior began to occur at concentrations higher than 16.2°Brix. Experimental data could best be predicted by adjusting an empirical model which consists of a single equation that takes into account the dependence of rise in boiling point on pressure and concentration.
Keywords: Concentration; Evaporation; Vapor pressure; Concentration (process); Food products; Fruit juices; Coffee extracts; Heat transfer